KAJIAN KOMPARATIF MENGENAI PENGERTIAN AL-QUR'AN MENURUT MUFASSIR KLASIK DAN KONTEMPORER - Hasibuan, Rizky Ahmadi; Nasution, Abdul Riswan; Arif, Muhammad; Harahap, Efridawati (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This article examines the concept of the Qur’an from the perspectives of both classical and contemporary exegetes, focusing on its epistemological, theological, historical, and methodological dimensions. It explores the evolution of the definition of the Qur’an-from a normative-theological framework toward historical-critical and hermeneutical approaches-and analyzes how this shift has influenced interpretive paradigms. The study employs a descriptive-comparative method through the analysis of classical exegetical works by scholars such as al-Tabari, al-Suyuti, al-Zarkashi, al-Baqillani, and al-Ghazali, alongside contemporary thinkers including Muhammad Abduh, Fazlur Rahman, Nasr Hamid Abu Zayd, Muhammad Arkoun, Muhammad Iqbal, Harun Nasution, and Farid Esack. The findings reveal that classical exegetes emphasize the purity of revelation, the authority of transmission, and the function of worship, whereas contemporary exegetes highlight social, ethical, and contextual relevance. The study’s main contribution lies in proposing an integrative framework that harmonizes both approaches, thus offering a balanced epistemological foundation between textual authenticity and the actualization of the Qur’an’s teachings in modern society